Kisah dalam Alquran Perspektif Pendidikan Islam - Majid, Muhammad Syahdan; Rohman, Abdul (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2022)
Allah has various ways of educating humans, one way of educating humans is by using the story method in the Qur'an. With this method, humans can take the moral message in the story. Even educational messages will be easy to digest because of the interesting stories in the Koran. The story in the Koran contains a lot of wisdom in which the wisdom is addressed to all humans. The wisdom behind these stories is full of educational value and can be a guide for every education practitioner, especially teachers. The series of stories from the Koran not only contain lessons for human life, the stories in the Koran can also be used as material for teaching and learning methods in an educational process. This paper aims to find educational values contained in the stories of the Koran through literature review. The educational values obtained in the story of the Koran include monotheism, intellectual, moral, sexual, spiritual, democratic, and parenting education.